2009
DOI: 10.4141/cjps08164
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation of lignin biosynthesis pathway in Brassica napus (canola) plants using RNAi

Abstract: 2009. Perturbation of lignin biosynthesis pathway in Brassica napus (canola) plants using RNAi. Can. J. Plant Sci. 89: 441Á453. Brassica napus meal contains high levels of lignin, which is one of the most important compositional factors affecting feed utilization by ruminants. We attempted to modify the concentration and composition of lignin in B. napus plants using the RNAi approach. Four genes were targeted for silencing by this approach either independently or in combination; caffeic acid O-methyltransfera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 39 publications
(32 reference statements)
0
14
0
1
Order By: Relevance
“…We recently showed that it was possible to aVect lignin (polymerized monolignols) content and composition in B. napus by altering the expression of genes in the phenylpropanoid pathway (Bhinu et al 2009b). While diVerences in the composition are beyond the scope of this work, we determined the lignin content in lines with mutations in the two genes.…”
Section: Resultsmentioning
confidence: 98%
“…We recently showed that it was possible to aVect lignin (polymerized monolignols) content and composition in B. napus by altering the expression of genes in the phenylpropanoid pathway (Bhinu et al 2009b). While diVerences in the composition are beyond the scope of this work, we determined the lignin content in lines with mutations in the two genes.…”
Section: Resultsmentioning
confidence: 98%
“…RNAi targeting of COMT reduced lignin content by 6.4–14.7% in switchgrass [4, 29, 30]. Other research has reported greater reductions of lignin content of 20% in alfalfa [13], 35% in Brassica napus [62] and 40% in canola [28]. …”
Section: Discussionmentioning
confidence: 99%
“…RNAi downregulation of COMT expression in canola [28], alfalfa [12, 13], switchgrass [4, 29, 30], and sugarcane [31, 32] consistently resulted in decreases in S monomers, as well as an overall decrease in total lignin content. Similar results have been found after sense or antisense downregulation of COMT in alfalfa [14, 23, 33, 34], poplar [35], tobacco [20], and maize [36, 37].…”
Section: Introductionmentioning
confidence: 99%
“…Bhinu et al (2009) cambiaron la vía metabólica de la lignina en la semilla de Brassica napus L. (canola) y llevó a la formación de lignina con una mayor concentración de grupos aldehídos.…”
Section: Discussionunclassified